Children's Roles in Tuberculosis Treatment Regimes. (26th June 2013) - Hunleth, Jean
<x xml:space="preserve">Abstract</x> In Zambia, the burden of HIV‐related diseases such as tuberculosis has received substantial international attention. Zambians experience and participate in a range of globally produced programs to manage TB and cure TB sufferers. Guided by WHO's Directly Observed Treatment, Short‐course protocol, TB treatment regimens now emphasize adherence to medications as the primary way to achieve cure. This article aims to understand how adherence models enter into the daily lives of children who live with and care for adult TB patients in an area disproportionately affected by the disease. I suggest that children domesticate adherence models, using them as strategies to safeguard identities, relationships, livelihoods, and futures that are increasingly under threat in the age of HIV. They draw on TB treatment and the hope and agency it affords to hold onto a version of childhood in which they are cared for by adults who will advocate for their well‐being.